The problem of formation of the basics of natural-scientific functional literacy in children in pedagogical theory and practice - Galinger N. A. (Educational environment today: development strategy, 2023)
Our research is devoted to the study, analysis and generalization of the information presented in the psychological and pedagogical literature on the problem of the formation of the foundations of natural-scientific functional literacy in children. The main tasks and a number of important pedagogical and developmental reasons for the formation of the foundations of natural-scientific functional literacy in preschool children are considered
Keywords: дошкольный возраст; функциональная грамотность; грамотность; preschool age; literacy; естественно-научная функциональная грамотность; functional literacy; natural science functional literacy